Penerapan Akuntansi Pada Usaha Mikro Kecil dan Menengah (UMKM) Khususnya Usaha Kemplang Krupuk Ikan Gabus Mang Arsyad dan UMKM Pempek Kemplang Krupuk Nona - Saekarini Yuliachtri; Rosalina Ghozali; Darma Yanti; Nina Sabrina (Journal of Dedicators Community, 2019)
Partners in the implementation of this service Kemplang UMKM Gabus Fish Krupuk Mang Arsyad and UMKM Pempek Kemplang Krupuk Nona located in the jayalaksana hall of the village 3-4 Ulu subdistrict opposite ulu 1. Based on the situation analysis, it can be identified several problems faced by partners, namely: The level of management and accounting knowledge is very minimal in both partners. This is motivated by the level of education of partner managers who are educated with junior high school education and the highest senior high school. The implementation method used in conducting school management management activities as well as structuring school financial statement structuring consists of 2 stages. namely stage 1 delivery of material, stage 2 guidance and assistance in preparing financial statements. UMKM accounting training activities for micro, small and medium enterprises (UMKM) to improve the company's financial performance run smoothly. All participants enthusiastically participated in the event until it was finished and felt the benefits of training for their business progress, gradually the process of preparing financial statements began to be carried out in the mentoring stage